A Concise Guide to cDNA Microarray Analysis. (September 2000) - Hegde, P.; Qi, R.; Abernathy, K.; Gay, C.; Dharap, S.; Gaspard, R.; Hughes, J.E.; Snesrud, E.; Lee, N.; Quackenbush, J.
Microarray expression analysis has become one of the most widely used functional genomics tools. Efficient application of this technique requires the development of robust and reproducible protocols. We have optimized all aspects of the process, including PCR amplification of target cDNA clones, microarray printing, probe labeling and hybridization, and have developed strategies for data normalization and analysis.